Cyberspaces and global affairs - Costigan, Sean S.; Perry, Jake (Ashgate Routledge, 2012)
With the rise of the social web and applications like Facebook, YouTube and Twitter, scholars and practitioners of international affairs are adapting to this new information space across a wide scale of issue areas. This book includes essays that explore such issues as networks and networked thinking, information ownership, and censorship.